A novel non-segmented inverted water outline rendering method can improve the tracking of responsible blood vessels for hemifacial spasm - Zhenzhu, Li; Jingfeng, Zhang; Wei, Zhou; Jianjun, Zheng; Yinshui, Xia (Frontiers in Neuroscience, 2024)
This study aimed to explore a novel, non-segmented based on inverted water outline, and rapid 3D rendering method for identifying the responsible blood vessels for hemifacial spasm. First, the software was developed using the free and open-source 3D Slicer to process magnetic resonance images. Outlines of the water region were extracted and rendered in a three-dimensional space. The traditional image re-slicing technique (IMRT) was used for the control group, while non-segmented inverted water outline rendering (NSIWR) was used to observe the relevant blood vessels in the root entry/exit zone (REZ) of patients with hemifacial spasm. The intraoperative exploration results were considered the gold standard for comparing the differences in identifying relevant blood vessels between the two methods. Twenty-five patients were included, and the reconstruction effect evaluation suggested that NSIWR could effectively reconstruct the responsible blood vessels of the cochlea, facial nerve, and REZ. Compared with IMRT, NSIWR effectively improved the diagnosis of the responsible blood vessels in the REZ, clarified their sources and directions, and was consistent with intraoperative results. This study introduced a novel rapid rendering method based on NSIWR, which was successfully applied for hemifacial spasm. The method enhances accuracy in identifying responsible blood vessels in the REZ without needing multi-modal techniques. It has the potential to improve surgical effectiveness and reduce exploration time in treating hemifacial spasm.